Architectural cognition cards: a card-based method for introducing spatial cognition research and user-centred thinking into the design process. (4th March 2022) - Mavros, Panagiotis; Conroy Dalton, Ruth; Kuliga, Saskia; Gath Morad, Michal; Robson, Simon; Hölscher, Christoph
Abstract : In this article, we present the rationale, development and preliminary evaluation of a novel set of materials to encourage and improve the consideration of users and their needs during the process of architectural design. Our focus is specifically on two areas: user-centred design principles and spatial cognition research. To this end, we developed two decks of flash-cards, termed the Architectural Strategies Cards (72 cards) and the Spatial Cognition Cards (111 cards). We conducted preliminary evaluations of the cards in the design studio and in design thinking workshops with multidisciplinary groups of students and with architectural practitioners. Our results suggest that the cards improve designers' immersion into the perspective of building-users in a playful way and introduce scientific concepts effectively. In conclusion, we argue that serious-games and card-based methods should be part of the multiple approaches necessary to encourage and improve user-centred thinking, and integrate research findings into evidence-based design at large.